Mitochondria- and Oxidative Stress-Targeting Substances in Cognitive Decline-Related Disorders: From Molecular Mechanisms to Clinical Evidence. (12th May 2019) - Lejri, Imane; Agapouda, Anastasia; Grimm, Amandine; Eckert, Anne
Abstract : Alzheimer's disease (AD) is the most common form of dementia affecting people mainly in their sixth decade of life and at a higher age. It is an extensively studied neurodegenerative disorder yet incurable to date. While its main postmortem brain hallmarks are the presence of amyloid- β plaques and hyperphosphorylated tau tangles, the onset of the disease seems to be largely correlated to mitochondrial dysfunction, an early event in the disease pathogenesis. AD is characterized by flawed energy metabolism in the brain and excessive oxidative stress, processes that involve less adenosine triphosphate (ATP) and more reactive oxygen species (ROS) production respectively. Mitochondria are at the center of both these processes as they are responsible for energy and ROS generation through mainly oxidative phosphorylation. Standardized Ginkgo biloba extract (GBE), resveratrol, and phytoestrogens as well as the neurosteroid allopregnanolone have shown not only some mitochondria-modulating properties but also significant antioxidant potential in in vitro and in vivo studies. According to our review of the literature, GBE, resveratrol, allopregnanolone, and phytoestrogens showed promising effects on mitochondria in a descending evidence order and, notably, this order pattern is in line with the existing clinical evidence level for each entity. In this review, the effects of these four entities are discussed with special focus on their mitochondria-modulating effects and their mitochondria-improving and antioxidant properties across the spectrum of cognitive decline-related disorders. Evidence from preclinical and clinical studies on their mechanisms of action are summarized and highlighted.